[(3)H]-adenosine nucleotide and [(3)H]-horadrenaline uptake by cold stored guinea-pig taenia caecum; Mechanical effects and release of [(3)H]-adenosine nucleotide by noradrenaline, papaverine, and nitroglycerine - Kuchii, M. (1973)
1. Cold storage (2° C) treatment progressively reduced noradrenaline uptake by the taenia caecum of the guinea-pig. After 15 days of cold treatment, [(3)H]-noradrenaline uptake by tissue was reduced to about 10% of control. On the other hand, prolonged cold storage failed to decrease [(3)H]-adenosine uptake by the taenia caecum. 2. Cocaine (10 μM) inhibited noradrenaline uptake by about 82% but nucleoside uptake was inhibited by 20%. Cocaine treatment failed to decrease the residual noradrenaline uptake in the cold stored strips (more than 10 days). Phenoxybenzamine (1 μM) or oligomycin (1 μg/ml) treatment decreased the tissue adenosine uptake to about 34% and 28% of the respective controls. 3. Based on thin layer chromatography, it was estimated that approximately 68% of [(3)H]-adenosine was converted into and retained as [(3)H]-ATP in the fresh tissues, a small fraction was accountable as [(3)H]-adenosine (18%) but virtually no [(3)H]-AMP, [(3)H]-cyclic AMP or [(3)H]-ADP was detected. Similar distribution of radioactivity of nucleotides was observed in tissues cold stored for 8 days. 4. The inhibition of the mechanical activity of taenia by noradrenaline (10 μM), papaverine (100 μM) and nitroglycerine (100 μM) was accompanied by [(3)H]-adenine nucleotide but not [(3)H]-noradrenaline release. Treatment with phentolamine and propranolol (both 1 μM) had no effect on the adenine nucleotide release elicited by nicotine and electrical field stimulation, whereas such treatment reduced the inhibitory action of both stimuli. 5. These results suggest that the nucleotide release after application of electrical and chemical stimulation may be from an extraneurogenic source. Thus, we conclude that ATP or a related nucleotide is not the chemical transmitter of the non-adrenergic inhibition in the taenia caecum of the guinea-pig.